2014
DOI: 10.1007/s00431-014-2306-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent lymphadenopathy in children with Kikuchi-Fujimoto disease

Abstract: Our results suggest that recurrent KFD is more frequent than reported, and recurrent KFD should be considered in children with a history of other systemic illnesses such as immune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…KFD has a reported recurrence rate of 3–4% in adults, while studies in children with KFD have shown high recurrence rates of up to 42.4% . None of the patients in the case series by Lin et al .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…KFD has a reported recurrence rate of 3–4% in adults, while studies in children with KFD have shown high recurrence rates of up to 42.4% . None of the patients in the case series by Lin et al .…”
Section: Discussionmentioning
confidence: 93%
“…6 Paediatric studies have shown a higher recurrence rate of up to 42.4%. 5,[7][8][9][10][11][12] There have also been reports of progression to SLE. 1,[13][14][15] The primary aim of this study was to investigate the clinical characteristics of children with KFD and to assess the recurrence of this disease.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evaluation of these relationships, however, is necessary. To the best of our knowledge, all seven previously reported cases of KD associated with HT occurred in females between the ages of 17 and 30 [1-4]. Three of these patients were diagnosed with HT before an episode of KD, whereas four patients were diagnosed with concurrent HT and KD.…”
mentioning
confidence: 99%
“…The etiology of KD remains controversial, but autoimmune disorders including systemic lupus erythematous, tend to develop before, simultaneously, or after an episode of KD [2]. However, only a few KD cases have been reported with autoimmune thyroiditis [1-4]. Here, we report a case of a male patient with concurrent Hashimoto’s thyroiditis (HT) and KD.…”
mentioning
confidence: 99%